Features of Processing of Ceramic Materials by an Electromagnetic Field - Klishin A.; Kovantsev A. S. Aleksander Sergeevich; Rudnev S. V. Stanislav Vasilievich; Zakutaev A.; Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich (Chemical Technologies, 2014)
Title screen